Phosphoinositide 3‐kinase δ is a regulatory T‐cell target in cancer immunotherapy - Lim, Ee Lyn (Immunology, 2019)
Tumour infiltration by regulatory T (Treg) cells contributes to suppression of the anti‐tumour immune response, which limits the efficacy of immune‐mediated cancer therapies. The phosphoinositide 3‐kinase (PI3K) pathway has key roles in mediating the function of many immune cell subsets, including Treg cells. Treg function is context‐dependent and depends on input from different cell surface receptors, many of which can activate the PI3K pathway. In this review, we explore how PI3Kδ contributes to signalling through several major immune cell receptors, including the T‐cell receptor and co‐stimulatory receptors such as CD28 and ICOS, but is antagonized by the immune checkpoint receptors CTLA‐4 and PD‐1. Understanding how PI3Kδ inhibition affects Treg signalling events will help to inform how best to use PI3Kδ inhibitors in clinical cancer treatment.